On the (k,s)-Hilfer-Prabhakar Fractional Derivative With Applications to Mathematical Physics - Samraiz, Muhammad; Perveen, Zahida; Rahman, Gauhar; Nisar, Kottakkaran Sooppy; Kumar, Devendra (Frontiers in Physics, 2020)
In this paper, we introduce the (k; s)-Hilfer Prabhakar fractional derivative. We discuss its properties and find a generalized Laplace transform of this operator. Furthermore, we show the applications of the (k; s)-Hilfer Prabhakar derivative in mathematical physics such as heat equation, free-electron laser equation, and kinetic differ-integral equation.